The B1 Domain of Streptococcal Protein G Serves as a Multi-Functional Tag for Recombinant Protein Production in Plants - Song, Shi-Jian; Diao, Hai-Ping; Moon, Byeongho; Yun, Areum; Hwang, Inhwan (Frontiers in Plant Science, 2022)
Plants have long been considered a cost-effective platform for recombinant production. A recently recognized additional advantage includes the low risk of contamination of human pathogens, such as viruses and bacterial endotoxins. Indeed, a great advance has been made in developing plants as a “factory” to produce recombinant proteins to use for biopharmaceutical purposes. However, there is still a need to develop new tools for recombinant protein production in plants. In this study, we provide data showing that the B1 domain of Streptococcal protein G (GB1) can be a multi-functional domain of recombinant proteins in plants. N-terminal fusion of the GB1 domain increased the expression level of various target proteins ranging from 1.3- to 3.1-fold at the protein level depending on the target proteins. GB1 fusion led to the stabilization of the fusion proteins. Furthermore, the direct detection of GB1-fusion proteins by the secondary anti-IgG antibody eliminated the use of the primary antibody for western blot analysis. Based on these data, we propose that the small GB1 domain can be used as a versatile tag for recombinant protein production in plants.